A numerical approach on achieving uniform thickness distribution in pressure thermoforming. (August 2019) - Patil, Jeet P.; Nandedkar, Vilas; Saha, Sandip; Mishra, Sushil
Abstract: Pressure thermoforming is one of the most widely used thermoplastic processing technique where a polymer sheet is deformed using gas pressure. Pressure forming is not suitable in applications such as airplane canopies where precise control over dimensions is required, because of the drawback of uneven thickness distribution of the product. The current work seeks to find a way to use the pressure forming technique to produce components having uniform thickness distribution. The deformation process of PMMA sheet into a hemispherical dome using pressure thermoforming is numerically analyzed and the concept of provision of initial thickness distribution to the sheet is proposed.